Enhanced Extrinsic Calibration Method for Camera-LiDAR Fusion and Monitoring of Safety Threats to Power Transmission Lines - Y. Lao; S. Wei; S. Wei; G. Liu; C. Liu; T. Yang (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Collision detection for ensuring safe navigation around power transmission lines is a critical task for maintaining operational safety. With advancements in sensor technology, cameras and LiDAR have been increasingly utilized for monitoring potential safety hazards associated with power lines. However, a single, fixed-position sensor may be insufficient to capture adequate information for accurately estimating the spatial relationship between transmission lines and mechanical equipment. To address this limitation, this paper proposes a method for measuring the spatial distance between transmission lines and mechanical equipment based on the simultaneous estimation of the relative position and orientation (extrinsic calibration) of the camera-LiDAR system. First, an enhanced extrinsic calibration technique for the camera-LiDAR system is introduced to effectively mitigate the impact of data noise on calibration results. Then, based on the calibration results, a spatial distance measurement method is developed to achieve more accurate distance calculations. Experimental evaluations using real-world data across various scenarios demonstrate that the proposed method exhibits strong robustness and accuracy, making it highly valuable for power transmission line safety monitoring and risk assessment.